A Quantitative Approach to the Wealth of Ottoman Women - Sema Keleş Yıldız (Tarih Dergisi)
This article quantitatively examines women’s wealth in İstanbul in the first half of the 18th century, using inheritance records extracted from İstanbul Court Registers. This study aims to analyze the economic status of women and the factors influencing them based on wealth-related data. This study starts with a general assessment of the wealth distribution in İstanbul in the first half of the 18th century, followed by an interpretation of individual wealth by gender. The present study also tries to explain the gender wealth gap (GWG) by linking it to the sources of women’s wealth. Additionally, it attempts to profile wealthy women, examine their wealth sources and components, and assess the relationship between titles and wealth. In the present study, quantitative findings were interpreted statistically, supported by qualitative findings. In addition, Mann-Whitney U and Kruskal-Wallis H tests were applied to determine whether there is a statistically significant difference between gender-wealth, debt-wealth, and title-wealth variables. As a result, it is concluded that women’s limited sources of wealth accumulation play a crucial role in creating a gender wealth gap between women and men in highwealth groups; the level of borrowing by gender influences the difference in the gender wealth gap between total and net wealth, and a significant relationship exists between women’s title and their wealth.